Relationships between campus experiences, practice experiences, long-term motivation and turnover intentions among Faroese student teachers - Elstad, Eyvind; Harryson, Hans; Christophersen, Knut Andreas Abben; Turmo, Are (2023)
Teacher education comprises subject education, pedagogical studies and training in schools. This complexity is demanding for all teacher training institutions. The present study examines empirical relationships in teacher education in the Faroe Islands. It explores the associations between the relevance of campus pedagogy studies, the integration of theory and practice during field experiences and the provision of personalised support by school practice supervisors. Structural equation modelling is employed to analyse the results of a survey of 105 student teachers and reveals positive links between both the relevance of campus teaching and practice mentors’ integration of theory and student teachers’ long-term motivation. However, no relationship is observed between personalised support from practice mentors and student teachers’ long-term motivation. As anticipated, the relevance of campus teaching, integration of theory by practice mentors, and the level of personalised support are negatively associated with intentions to discontinue teacher education. Relationships between campus experiences, practice experiences, long-term motivation and turnover intentions among Faroese student teachers